Individual Differences in Learning and Remembering - Elfi Churnia; Neviyarni Neviyarni (Journal of Counseling, Education and Society, 2021)
Humans are unique creatures, have differences from one another. Whether it's differences in race, ethnicity, personality, hair color, etc. No human being in this world is exactly the same, each individual is different from one another. Individual differences are a gift from Allah SWT because these differences can produce extraordinary character and intelligence in each individual. In terms of learning and remembering, individuals also have different characteristics. Therefore, as an educator, teachers are expected to be able to understand and understand the understanding of each student in order to know how to distinguish each of these differences in a good direction. This article looks at individual differences in Learning and Remembering